A genome‐wide SNP scan reveals two loci associated with the chicken resistance to Marek's disease. (20th July 2012) - Li, D. F.; Lian, L.; Qu, L. J.; Chen, Y. M.; Liu, W. B.; Chen, S. R.; Zheng, J. X.; Xu, G. Y.; Yang, N.
Summary Marek's disease (MD) is a neoplastic disease in chickens, caused by the Marek's disease virus (MDV). To investigate host genetic resistance to MD, we conducted a genome‐wide association study (GWAS) on 67 MDV‐infected chickens based on a case and control design, including 57 susceptible chickens in the case group and 10 resistant chickens as controls. After searching 38 655 valid genomic markers, two SNPs were found to be associated with host resistance to MD. One SNP, rs14527240, reaching chromosome‐wide significance level (P < 0.01) was located in the SPARC‐related modular calcium‐binding 1 (SMOC1) gene on GGA5. The other one, GGaluGA156129, reaching genome‐wide significance (P < 0.05), was located in the protein tyrosine phosphatase, non‐receptor type 3 (PTPN3) gene on GGA2. In addition, expression patterns of these two genes in spleens were detected by qPCR. The expression of SMOC1 was significantly up‐regulated (P < 0.05), whereas the expression of PTNP3 did not show significance when the case group was compared with the control group. Up‐regulation of SMOC1 in susceptible spleens suggests its important roles in MD tumorigenesis. This is the first study to investigate MD‐resistant loci, and it demonstrates the power of GWASs for mapping genes associated with MD resistance.